Respuesta :

Answer:

  • (x -1)(x +6)
  • (x -5)(x +3)
  • (x -4)(x -3)

Step-by-step explanation:

In each case, you're looking for divisors of the constant that have a sum equal to the x-coefficient. Those divisors are the constants in the binomial factors.

1) -6 = -1·6 = -2·3 . . . . . (-1)+(6) = 5, so these are the constants of interest.

  x^2 +5x -6 = (x -1)(x +6)

__

2) -15 = -1·15 = -3·5 = -5·3 . . . . . (-5)+(3) = -2, so these are the constants of interest

  x^2 -2x -15 = (x -5)(x +3)

__

3) 12 = -1·-12 = -2·-6 = -3·-4 . . . . . (-3) +(-4) = -7, so these are the constants of interest

  x^2 -7x +12 = (x -3)(x -4)